Pengaruh Manajemen Kurikulum Berbasis Kompetensi terhadap Kompetensi Soft Skills dan Hard Skills Lulusan SMA - Pertiwi, Ila Indah; Eljohn, Grace; Fitriah, Nur Indriana; Warman, Warman (ALSYS, 2025)
The Competency-Based Curriculum (KBK) approach is one of the solutions that is expected to be able to answer the needs of the times. However, reality shows that many high school graduates still face challenges in optimally integrating hard skills and soft skills. This study aims to analyze the influence of Competency-Based Curriculum management on the development of soft skills and hard skills competencies of high school graduates. This study uses a quantitative approach with a survey method to analyze the influence of Competency-Based Curriculum management on the development of soft skills and hard skills of high school graduates. This study shows that the management of the Competency-Based Curriculum (KBK) at the high school level has a significant positive influence on the development of students' soft and hard skills. From the aspect of curriculum management, planning obtained the highest score (85 out of a scale of 100), followed by implementation (80) and evaluation (78), which shows that the school has made optimal efforts in designing and implementing KBK, although the evaluation stage still needs improvement. In the development of soft skills, communication and cooperation skills received the highest scores of 85 and 84, respectively, while leadership and time management obtained scores of 75 and 72. On the other hand, students' mastery of hard skills is also in the good category with the highest score on technology-based skills (86) and the lowest score on analytical skills (74). The results of the linear regression test confirmed that there was a significant positive relationship between KBK management and the mastery of soft skills (regression coefficient 0.65; p < 0.01) and hard skills (regression coefficient 0.59; p < 0.01).